Pengaruh Builder Design Pattern Pada Performa Aplikasi Dengan Menggunakan Bahasa Pemrograman Golang - Nabila Khairunisa; Raden Mohamad Rishwan; Raihan Akbar Saputro; Carudin Carudin (Universitas Komputer Indonesia, 2024)
In the industrial era 4.0, technological developments are increasingly progressing, including the field of software engineering. Therefore, a solution is needed to overcome problems during software development, especially application performance. The solution uses design patterns, one of them is the builder design pattern. The Builder Design Pattern is a design pattern in the world of programming that is used to simplify the process of creating complex objects by breaking and breaking code into simpler parts. The method used in this study is an experimental approach, in which researchers look for the influence between variables by using the benchmark evaluation method. This research was conducted by creating two program codes, one using the Builder Design Pattern and the other without using the Builder Design Pattern. Then, the two codes are tested using several performance metrics such as execution time and memory usage. The results of this research show that the use of the Builder Design Pattern can significantly affect performance in some cases. Therefore, the use of the Builder Design Pattern must be considered properly depending on the needs of the application being built to produce an application with maximum performance. Key Words: Design Pattern, Builder Design Pattern, Benchmark, Execution Time